2021
DOI: 10.1007/s41348-021-00432-3
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan induces delayed grapevine defense mechanisms and protects grapevine against Botrytis cinerea

Abstract: In the present study, a commercial chitosan soluble in acid solution and obtained from shrimp shell waste, with a molecular weight of 173 kDa and a degree of acetylation of 17%, named as chitosan (173/17), was investigated. Chitosan is a well-known biopolymer whose antimicrobial properties are highly influenced by the molecular weight, degree of acetylation as well as the preparation and derivatization methods used. Chitosan (173/17) was applied on grapevine leaves before Botrytis cinerea inoculation to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…'Chardonnay' leaves and bunch rot in commercial wine grapes (Reglinski et al, 2010). De Bona et al (2021) confirmed the fungistatic and filmogenic properties of chitosan in potted plants. During the first days after treatment, chitosan acted as a physical barrier to fungal attack and inhibited its growth.…”
Section: Grey Mould (Botrytis Cinerea)mentioning
confidence: 70%
“…'Chardonnay' leaves and bunch rot in commercial wine grapes (Reglinski et al, 2010). De Bona et al (2021) confirmed the fungistatic and filmogenic properties of chitosan in potted plants. During the first days after treatment, chitosan acted as a physical barrier to fungal attack and inhibited its growth.…”
Section: Grey Mould (Botrytis Cinerea)mentioning
confidence: 70%
“…This suggests that dosages, number of applications, and investigated strains play a crucial role in nanomaterials interactions with fungal cells. Chitosan solution has also showed good antimicrobial and filmogenic properties protecting from B. cinerea infection through specific defence mechanisms [ 81 , 82 ]. In fact, the value of mycelial growth in nanoCaCO 3 @PAE 36.0 mm was much higher than 17.0 recorded in nanoCaCO 3 @PAE@CH.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, brown rot caused by the necrotrophic fungus M. fructicola is a major disease for peach fruit [ 24 ]. Natural resistance inducers have been proposed as an alternative and innovative approach for efficient disease control in crops [ 27 ]. Among them, chitosan, a versatile compound, is known, even at very low concentrations, to show direct antifungal activity and trigger, as a non-microbial elicitor, the defense mechanisms in plants that are challenged by pathogens [ 11 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%